A PREDICTIVE MODEL (ETLM) FOR AS(III) ADSORPTION AND SURFACE SPECIATION ON OXIDES CONSISTENT WITH SPECTROSCOPIC DATA - Sverjensky D.A.; Fukushi K. (My University, 2006)
Arsenic(III) adsorption reactions are thought to play a critical role in the mobility of arsenic in the environment. It is the nature of the As(III) surface species that must be known on a wide variety of minerals and over a range of pH, ionic strength and surface coverage in order to be able to predict adsorption behavior. EXAFS and XANES spectroscopic studies have identified bidentate, binuclear inner-sphere surface species and/or an outer-sphere species, but only a few oxides have been examined. These results need to be integrated with a predictive surface complexation model in order to ascertain the environmental conditions under which the different surface species may be important on a wide range of solids. In the present study, the surface species information from XAFS and XANES studies has been built into a recent extension of the triple-layer model (ETLM) for the formation of inner-sphere complexes of anions that takes into account the electrostatics of water dipole desorption during ligand exchange reactions. The ETLM has been applied to regress surface titration, proton coadsorption, and As(III) adsorption data over extensive ranges of pH, ionic strength, electrolyte type and surface coverage for magnetite, goethite, gibbsite, amorphous hydrous alumina, hydrous ferric oxide (HFO), ferrihydrite, and amorphous iron oxide. Two principal reactions forming inner- and outer-sphere As(III) surface species,2 > SOH + As(OH)30 = (> SO)2 As(OH)0 + 2 H2 Oand> SOH + As(OH)30 = > SOH2+ _ AsO(OH)2-,respectively, were found to be consistent with most of the data. The proportions of these species vary systematically. Under some circumstances, on ferrihydrite, am.FeO, and HFO an additional inner-sphere deprotonated, bidentate, binuclear species and an additional outer-sphere species represented by2 > SOH + As(OH)30 = (> SO)2 AsO- + H+ + 2 H2 Oand2 > SOH + H+ + As(OH)30 = (> SOH2+)2 _ AsO(OH)2-,respectively, were needed. Expressing the equilibrium constants with respect to internally consistent site-occupancy standard states for As(III) adsorption on different solids permits systematic differences to be examined and explained with Born solvation theory. As a result, a set of predictive equations for As(III) adsorption equilibrium constants on all oxides, including both amorphous and poorly crystalline oxides, enables prediction of the surface speciation of As(III) over wide ranges of pH, ionic strength, electrolyte type and surface coverage.
Keywords: ADSORPTION; ARSENIC; ENVIRONMENTAL CONDITIONS; SPECIATION (CHEMISTRY); XANES SPECTROSCOPY